Compliment And Compliment Response In Instagram - Khalifah, Amalia; , Agus Wijayanto, Ph.D; , Dr. Anam Sutopo, M.Hum (2015)
This study focuses on analyzing compliment and compliment response in Instagram. This study aims to (1) describe the categories of compliment in Instagram, (2) clarify the types of compliment response in Instagram, and (3) describe the intentions of compliment in Instagram. This research applies descriptive qualitative method. The data analyzed are comments containing compliment and compliment response in Instagram. Based on the analysis the writer found that; (1)The compliment in this research is divided into two; linguistic and non-linguistic strategies. The linguistic strategy is aparted into two caategories; possession compliment and performance compliment. There are two compliment categories of compliment strategies which are found in Instagram: possession compliment and performance compliment. The compliment givers in Instagram mostly use possession compliment, particularly, adjective possession compliment. The performance compliment category is rarely to use in Instagram. The compliment givers in Instagram also use non-linguistic compliment which is formed in emoticons. Smiley and love emoticons are the most emoticons emerge in this research. Some compliment givers use one emoticons and some other use more than one; (2)The intentions of compliment are to praise and to ask compliment back. (3) The compliment response which mostly use in Instagram is appreciation token strategy; thank you and thanks. Another compliment receivers in Instagram use non-lingustic compliment response as well. It is formed in emoticons. The most emoticons emerge in this research for responding compliment are thumbs, love and smiley emoticons. Some compliment receivers use one emoticon, and some other use more than one. The compliment givers and compliment receivers in this research use non-linguistic strategy of compliment, It because this research was held in computer mediated communication so that the way of the compliment giver gives a compliment and responds the compliment have to be very simple and short since people is limited by 160 characters of text. Most compliment giver prefer to use emoticons as emoticons has a lot of meanings so people do not need to type a lot of characters or people do not need to be limited by 160 characters. The using of emoticons in this research also make the time shorten than typing compliment by using words